Chemical analysis and in vitro UV‐protection characteristics of clays traditionally used for sun protection in South Africa. Issue 3 (7th May 2013) - Dlova, Ncoza C.; Nevondo, Funanani T.; Mwangi, Elizabeth M.; Summers, Beverley; Tsoka‐Gwegweni, Joyce; Martincigh, Bice S.; Mulholland, Dulcie A.
Summary Clays have been used in southern Africa as photoprotectants by the indigenous people. Typically, two types of clay are used: one white in colour and the other red. In this work, the two clays were identified and characterized, and their in vitro SPF values measured. The clays afford a low SPF but offer broad‐spectrum protection. No cutaneous side effects from the use of these clays are known. Further consideration should be given to the potential use of clays in sunscreen preparations.